2021
DOI: 10.1038/s41598-021-90385-2
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA in combination with HER2-targeting drugs reduces breast cancer cell viability in vitro

Abstract: HER2-positive (HER2 +) breast cancer patients that do not respond to targeted treatment have a poor prognosis. The effects of targeted treatment on endogenous microRNA (miRNA) expression levels are unclear. We report that responsive HER2 + breast cancer cell lines had a higher number of miRNAs with altered expression after treatment with trastuzumab and lapatinib compared to poorly responsive cell lines. To evaluate whether miRNAs can sensitize HER2 + cells to treatment, we performed a high-throughput screen o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 56 publications
1
15
0
Order By: Relevance
“…We have previously shown that overexpression of miR-101-5p reduces cell viability measured by CellTiter-Glo assay in HER2+ KPL4 breast cancer cells alone and in combination with lapatinib and trastuzumab. 20 These data were confirmed here using a complementary cell proliferation assay measuring the confluence over time after miR-101-5p overexpression. Indeed, miR-101-5p overexpression inhibited proliferation compared to the scrambled negative control (Student’s t -test, p < 0.001; Figure 2A ).…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…We have previously shown that overexpression of miR-101-5p reduces cell viability measured by CellTiter-Glo assay in HER2+ KPL4 breast cancer cells alone and in combination with lapatinib and trastuzumab. 20 These data were confirmed here using a complementary cell proliferation assay measuring the confluence over time after miR-101-5p overexpression. Indeed, miR-101-5p overexpression inhibited proliferation compared to the scrambled negative control (Student’s t -test, p < 0.001; Figure 2A ).…”
Section: Resultssupporting
confidence: 66%
“… 25 Previously, we have shown that miR-101-5p decrease cell viability in HER2+ breast cancer cells and sensitize the cells to targeted treatment. 20 The aim of the current study was to gain knowledge of the mechanisms involved in treatment response, by studying the effects on the proteomic landscape when combining miR-101-5p overexpression with HER2-targeting drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After that, 20 mL (5 g/L) of MTT (3-(4,5dimethyl-2-thiazolyl)-2,5-diphenyl-2-H-tetrazolium bromide) reagent was added to the designated wells. After a 4 h incubation, the MTT formazan precipitate was dissolved in dimethylsulphoxide (DMSO) (150 mL/well, Sigma-Aldrich, St. Louis, MO, USA) in a shaker for 5 min before reading the absorbance at 570 nm using a 96-well plate reader (Bio-Rad, Winooski, VT USA) (47)(48)(49).…”
Section: Cell Proliferation Assaymentioning
confidence: 99%
“…1A). Evidences showed that miR-NAs own great potentials in combination cancer therapy [29][30][31]. For example, targeting miR-21 could enhance conventional chemotherapeutic efficacy, together with overcoming drug resistance and cancer recurrence [32].…”
Section: Mir-138-1-3p Expression Was Reduced In Sorafenib-resistant Cells and May Participate In Resistance Developmentmentioning
confidence: 99%